(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe the nephrotoxicity characteristics in patients using vancomycin at An Giang Obstetrics and Children’s Hospital. Subjects and methods: Retrospective cohort study on 100 medical records of patients treated at An Giang Obstetrics and Children’s Hospital during the period from January 1st, 2020 to December 31st, 2020. Results: The rate of nephrotoxicity in the study was 24.0%. Median time to toxicity onset was 8 days, interquartile range 4-14 days from drug initiation. The rate of occurrence of nephrotoxicity at different levels: risk, damage and failure were 54.2%, 29.2% and 16.6%, respectively. 33.3% of patients who developed nephrotoxicity had reversible toxicity with a median time to toxicity recovery of 5.2 (3.2 - 14.8) days after the end of dosing. Conclusion: The rate of nephrotoxicity in the study was 24.0%. The rate of occurrence of nephrotoxicity at different levels: risk, damage and failure were 54.2%, 29.2% and 16.6%, respectively. 33.3% of patients with nephrotoxicity had reversible toxicity.